2020
DOI: 10.1136/bmjebm-2020-111492
|View full text |Cite
|
Sign up to set email alerts
|

Is there a smoker’s paradox in COVID-19?

Abstract: Although it is well established that cigarette smoking is associated with morbidity and mortality in several respiratory infections, data from recent studies suggest that active smokers are underrepresented among patients with COVID-19. This has led to claims that a ‘smoker’s paradox’ may exist in COVID-19, wherein smokers are protected from infection and severe complications of COVID-19. We aimed to review and summarise existing literature in this context. Electronic databases were searched for articles that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
141
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(156 citation statements)
references
References 44 publications
11
141
4
Order By: Relevance
“…This is in line with the well-known general correlation between smoking and increased prevalence and mortality of infectious diseases [291], and with the fact that many COPD patients are smokers [285]. One should keep in mind, though, that existing data on the prevalence of smokers among COVID-19 patients and on the association between the COVID-19 outcomes and smoking are rather contradictory [290]. In fact, although some studies showed that smokers are more susceptible to COVID-19, and smoking is associated with more severe disease outcomes [293], several other studies pointed out the underrepresentation of active smokers among the COVID-19 patients [290] and indicated that active smoking is not associated with the COVID-19 severity [294].…”
Section: Human (Host) Factorssupporting
confidence: 76%
See 4 more Smart Citations
“…This is in line with the well-known general correlation between smoking and increased prevalence and mortality of infectious diseases [291], and with the fact that many COPD patients are smokers [285]. One should keep in mind, though, that existing data on the prevalence of smokers among COVID-19 patients and on the association between the COVID-19 outcomes and smoking are rather contradictory [290]. In fact, although some studies showed that smokers are more susceptible to COVID-19, and smoking is associated with more severe disease outcomes [293], several other studies pointed out the underrepresentation of active smokers among the COVID-19 patients [290] and indicated that active smoking is not associated with the COVID-19 severity [294].…”
Section: Human (Host) Factorssupporting
confidence: 76%
“…Among different factors potentially affecting the susceptibility to SARS-CoV-2 and changing the outcomes and mortality amongst COVID-19 patients are smoking and vaping [285,[290][291][292]. This is in line with the well-known general correlation between smoking and increased prevalence and mortality of infectious diseases [291], and with the fact that many COPD patients are smokers [285].…”
Section: Human (Host) Factorsmentioning
confidence: 53%
See 3 more Smart Citations